Semaglutide as a potential therapeutic alternative for HNF1B-MODY: a case study - Almutair, Angham; Almulhem, Beshaier (Frontiers in Endocrinology, 2024)
Maturity-Onset Diabetes of the Young (MODY) is a grouping of monogenic disorders. It is characterized by dominantly inherited, non-insulin-dependent diabetes. MODY is relatively rare, encompassing up to 3.5% in those diagnosed under 30 years of age. Specific types are most commonly treated with sulfonylurea, particularly those identified as HNF4A-MODY and HNF1A-MODY. HNF1B-MODY is another type that is most frequently managed with insulin therapy but lacks a defined precision treatment. We present an 18-year-old, non-obese female diagnosed with HNF1B-MODY. She displays complete gene deletion, a renal cyst, and hypomagnesemia. Her treatment plan includes both long and short-acting insulin, though she frequently encountered hypoglycemia and hyperglycemia. Semaglutide, a GLP-1RA, administered weekly over 4 months. The patient's glucose was continuously tracked using Dexcom's Continuous Glucose Monitoring (CGM) system. The data suggested a notable improvement in her condition: time-in-range (TIR) increased from 70% to 88%, with some days achieving 100%, and the frequency of hypoglycemic episodes, indicated by time-below-range (TBR) values, fell from 5% to 1%, time-above-range (TAR) values also dropped from 25% to 10%, and her HbA1c levels declined from 7% to 5.6%.During the semaglutide therapy, we were able to discontinue her insulin treatment. Additionally, her body mass index (BMI) reduced from 24.1 kg/m 2 to 20.1 kg/m 2 .However, semaglutide treatment was halted after four months due to side effects of nausea, vomiting, and reduced appetite. Other contributing factors included exam stress and a COVID-19 infection, which forced a switch back to insulin. Her last recorded HbA1c level under exclusive insulin therapy rose to 7.1%, and her BMI increased to 24.9 kg/m 2 . In conclusion, semaglutide could potentially replace insulin to improve glucose variability, TIR, and HbA1c in patients with HNF1B-MODY.However, more extensive studies are required to confirm its long-term safety and efficacy.